Atypical Os trigonum syndrome: a case of FHL entrapment - Siddartha, Arunodhaya S.; Nataraj, Arjun (International Journal of Research in Orthopaedics, 2022)
Os trigonum is an accessory bony growth from posterior aspect of talus, which presents as swelling and pain behind the ankle causing hinderance to daily activities secondary to impingement. The overuse of ankle with repetitive stress on plantar flexion is usually seen in ballet dancers. Unusual cases can be seen irrespective of the profession and can be symptomatic. Sometimes symptomatic patients may improve with activity modification and rest. Syndromic involvement is featured by entrapment of FHL tendon. In that case, excision of the mass with entrapment release can improve the functional outcome.